The use of emetrics in strategic marketing decisions: a preliminary investigation. (28th August 2007) - Weischedel, Birgit; Matear, Sheelagh; Deans, Kenneth R.
Companies operating on the internet need appropriate metrics to support strategic marketing decisions. These metrics may relate to traditional performance measures but have the potential to include new metrics or new ways of collecting existing metrics. This paper addresses the question of how web-based companies can use emetrics for strategic marketing decisions. Specifically, it identifies some aspects of the current use of emetrics in strategic marketing decisions within the web environment. In a preliminary investigation, interviews with web-based business units revealed that companies currently measure website performance and consumer behaviour online but are uncertain how best to use those metrics to inform strategic marketing decisions. The findings suggest that businesses are looking for recommendations regarding management and choice of emetrics that will increase comparability among companies as well as overcome current data limitations.